COVID-19 and Obesity: An Epidemiologic Analysis of the Brazilian Data - Diego Assis Gonçalves; Victória Ribeiro; Ana Gualberto; Fernanda Peres; Michaela Luconi; Jacy Gameiro (International Journal of Endocrinology)
Brazil has the second highest number of deaths due to COVID-19. Obesity has been associated with an important role in disease development and a worse prognosis. We aimed to explore epidemiological data from Brazil, discussing the potential relationships between obesity and COVID-19 severity in this country. We used a public database made available by the Ministry of Health of Brazil (182700 patients diagnosed with COVID-19). Descriptive statistics were used to characterize our database. Continuous data were expressed as median and analyzed by the nonparametric tests Mann–Whitney or one-sample Wilcoxon. The frequencies of categorical variables have been analyzed by chi-square tests of independence or goodness-of-fit. Among the number of deaths, 74% of patients were 60 years of age or older. Patients with obesity who died of COVID-19 were younger (59 years (IQR = 23)) than those without obesity (71 years (IQR = 20), P<0.001, and η2 = 0.0424). Women with obesity who died of COVID-19 were older than men (55 years (IQR = 25) vs. 50 (IQR = 22), P<0.001, and η2 = 0.0263). Furthermore, obesity increases the chances of needing intensive care unit (OR: 1.783, CI: 95%, and P<0.001), needing ventilatory support (OR: 1.537, CI: 95%, and P<0.001 and OR: 2.302, CI: 95%, and P<0.001, for noninvasive and invasive, respectively), and death (OR: 1.411, CI: 95%, and P<0.001) of patients hospitalized with COVID-19. Our analysis supports obesity as a significant risk factor for the development of more severe forms of COVID-19. The present study can direct a more effective prevention campaign and appropriate management of subjects with obesity.